Development of Underwater Data Capturing Vehicle Platform - John Aqmal , Muhamad Nazmi Afzan; Sari, Suhaila; Md Taujuddin, Nik Shahidah Afifi; Roslan, Hazli; Mohd Muji, Siti Zarina (Evolution in Electrical and Electronic Engineering, 2024)
The invention of the underwater data capture vehicle platform marks a significant improvement in underwater research technology. The project sought to address issues associated with underwater data collection, such as image quality, water quality testing, and search and rescue operations. Using IoT technologies and modern equipment, the platform provides a full solution for monitoring and evaluating underwater environments. The project aim is to construct a moving platform with underwater data measurement equipment for underwater object recognition studies. The study also focuses on the remotely controlled conveyance of underwater research items. The project objectives include creating a moving platform and its measuring equipment arrangement, constructing an underwater data collection vehicle platform with an IoT application, and evaluating the platforms operation and data gathering procedures. This project was successful in designing and developing an underwater data gathering vehicle platform with Internet of Things (IoT) capabilities. The platform exhibited its capacity to float well with a weight on its surface, and the crane worked well for lowering research equipment and cameras underwater. Turbidity and underwater depth distance data were obtained at various depths and weather conditions, yielding vital information on water quality. Underwater images captured at different depths were successful and can further help to comprehend underwater conditions. Overall, this project met its goals and provided a complete solution for viewing and analyzing underwater conditions using current technologies and IoT.